Artificial Immune System Inspired Intrusion Detection System Using Genetic Algorithm - Aziz, Amira Sayed A.; Salama, Mostafa A.; Hassanien, Aboul ella; Hanafi, Sanaa El-Ola (Informatica)
Artificial Immune System Inspired Intrusion Detection System Using Genetic Algorithm